Humanistic psychology: From protest towards the transcendence - Kočiūnas, Rimas (Psichologija, 1993)
The article analyzes the assumptions of philosophic humanistic psychology and its development. The relation of humanistic psychology to other psychological approaches is introduced. The major theoretical assumptions of humanistic psychology, the input of the most important authors and their view of the person are introduced. The article presents the application aspects of humanistic psychology.
Keywords: humanistic psychology; Maslow; Rogers